2005 IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR'05) - Workshops
DOI: 10.1109/cvpr.2005.390
|View full text |Cite
|
Sign up to set email alerts
|

A Measure for Objective Evaluation of Image Segmentation Algorithms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 12 publications
(29 reference statements)
0
101
0
Order By: Relevance
“…While there exist many general purpose segmentation engines, studies have shown that none are particularly good at segmenting out individual objects [17,5]. Instead, we will follow [6,11] in using multiple different segmentations of the same image, in a way sampling the space of segmentations.…”
Section: Does Spatial Support Matter?mentioning
confidence: 99%
“…While there exist many general purpose segmentation engines, studies have shown that none are particularly good at segmenting out individual objects [17,5]. Instead, we will follow [6,11] in using multiple different segmentations of the same image, in a way sampling the space of segmentations.…”
Section: Does Spatial Support Matter?mentioning
confidence: 99%
“…These measures can be divided [23] into several classes: regionbased quality evaluation measures (taking into account the characteristics of the segmented regions), edge-based quality evaluation measures (taking into account the characteristics of boundaries of the segmented regions), measures based on information theory, and nonparametric measures. The first class includes the socalled directional Hamming distance [20], which is asymmetrical measure, and normalized Hamming distance [20], Local / global consistency errors [23], etc. The second class includes the precision and recall measures [21], earth movers distance [22], and others.…”
Section: Segmentation Quality Evaluationmentioning
confidence: 99%
“…This complicates the clear choice to any particular measure of the segmentation quality. Given the fact that the study of measures of segmentation quality is not the main purpose of this work, in this paper we use the consistency errors [23] and Rand index [24] as one of the most commonly used measures.…”
Section: Segmentation Quality Evaluationmentioning
confidence: 99%
“…It is important to evaluate the quality of a segmented image obtained by various clustering algorithm because the results of various clustering algorithms gives different results. The NPR index [23] is the generalized version of rand index, which is used to measure the quality of clustering results. The NPR uses the hand-labeled set of ground-truth segmentation to perform a comparison between two image segmentation algorithms.…”
Section: A Validation Measuresmentioning
confidence: 99%